Infeksi Ganda Leptospira dan Hantavirus pada Rattus norvegicus di Maumere Flores, Nusa Tenggara Timur - Arif Mulyono; Ristiyanto Ristiyanto; Dimas Bagus Wicaksono Putro (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2017)
Infection of Leptospirosis and Hantavirus are increased which related to global warming. Rattus norvegicus is reservoirs of both of diseases infections. Dual infection of Leptospira and Hantavirus in R. norvegicus become risk factor of Leptospira and Hantavirus infection in the human. The objective of this study is to figure out the prevalence of Dual infection in R. norvegicus. This study was descriptive research with cross-sectional design. The population of study was R. norvegicus in Maumere City, Flores. The rats (n=114) were trapped from perimeter and buffer area of Maumere Port, Flores in August to November 2014. Leptospira in R. norvegicus detected by PCR used specific primers for 16S rRNA gene and Hantavirus by nested – PCR used specific primers for the L segment. The data was analysed using descriptive analysis. The prevalence of Leptospira in R. norvegicus was 4.3%, hantavirus was 22,8% and dual infection of Leptospira and Hantavirus was 1.8%. The transmission dual infection of leptospirosis and Hantavirus are potentially occured in Maumere.